2012
DOI: 10.1111/j.1600-079x.2011.00958.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin pharmacokinetics following two different oral surge‐sustained release doses in older adults

Abstract: Melatonin is increasingly used for the treatment of sleep disorders. Surge-sustained formulations consisting of combined immediate release and controlled release dosing may mimic the endogenous melatonin physiologic profile. However, relatively little is known about the pharmacokinetic properties of low dose (<0.5 mg) and high dose (>2 mg) melatonin in a combined immediate release/controlled release dose, especially in older adults who may also exhibit altered melatonin disposition. To assess this, we conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 43 publications
(66 reference statements)
4
60
0
2
Order By: Relevance
“…Similar experiments that apply chronic melatonin treatment to obese individuals, those with impaired glucose tolerance or full type 2 diabetes are necessary to confirm and extend these observations. [136,155]. However, to target the melatonin signalling pathway with greater efficiency, several long-lasting high affinity MT1/MT2 receptor agonists have been developed [155][156][157][158].…”
Section: Clinical Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Similar experiments that apply chronic melatonin treatment to obese individuals, those with impaired glucose tolerance or full type 2 diabetes are necessary to confirm and extend these observations. [136,155]. However, to target the melatonin signalling pathway with greater efficiency, several long-lasting high affinity MT1/MT2 receptor agonists have been developed [155][156][157][158].…”
Section: Clinical Evidencementioning
confidence: 99%
“…Results from preclinical study of melatonin's effect on glucose homeostasis should be interpreted with caution. For one, the effective dose of melatonin is often exceedingly high (>5 mg/kg) and well above the recommended dosage used for the clinical treatment of sleep disorders (2-4 mg/day; [136]). Further, a caveat to studies in rodents is the obvious species divergence in the timing of melatonin secretion relative to food intake, peak insulin secretion and serum glucose.…”
Section: The Pancreatic Response To Melatoninmentioning
confidence: 99%
“…The review included five randomized clinical trials (RCT) [3,8,17,21,28], 16 cohort studies [9, 11-16, 18-20, 22, 23, 25-27, 29], and one case report [24]. Nineteen studies included healthy volunteers [8, 9, 11-15, 17-20, 22-29].…”
Section: Resultsmentioning
confidence: 99%
“…1. Twenty-two studies (n=359) were included in the review [3,8,9,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Table 1 describes number of volunteers/patients, study design, volunteer/patient characteristics, measuring period, and reported pharmacokinetic variables.…”
Section: Resultsmentioning
confidence: 99%
“…Exogenous melatonin has no reported tolerance, dependence, or 'hangover effect' [11], and no adverse effect on alertness or mood the following day [12], as well as minimal side-effects (e.g., headache, dizziness, nausea, drowsiness) [13,14] if administered at a low dose. [15] Melatonin has a short half-life of only 30-50 minutes and can induce phase shifts in the circadian timing system (both central and peripheral clocks) and when administered acutely, reduces core body temperature and lowers alertness, encouraging sleep propensity. [16] M A N U S C R I P T…”
Section: Melatonin Use In Sleep Disordersmentioning
confidence: 99%